Motivating students to enhance their second language speech pronunciation through selfvids: a case study of Malaysian secondary schoolers / Wan Munirah Wan Ahmad @ Wan A. Halim - Wan Ahmad @ Wan A. Halim, Wan Munirah (2015)
This research explored the motivation and enhancement of English language pronunciation among the form three students in a Malaysia secondary school through the use of selfvids. In Malaysia, many students are seen to having problems pronouncing certain English words when speaking. This obstructs understanding of other individuals on what is being communicated about. The teaching of pronunciation is scarcely given attention to in class, thus utilizing technology in language learning is essential to help the students enhance their pronunciation. This research was segregated into two phases where the first phase sees 25 participants (n=25) taking part in a pre-selfVid session. They were required to read an English text provided by the researcher while self-recording themselves. The second phase focused on only 6 cases for in-depth survey. Here, these cases had to go through an interview, a treatment and recording of the post-selfvid. The procedures were analysed to get the final data on pronunciation errors and its connection with motivation. The findings suggest high motivation with the cases deliberating on the importance of good pronunciation for various reasons. A majority of the cases also found that using selfvids can assist their English pronunciation learning in school. It is recommended that teachers be given freedom of teaching by allowing them to use selfvids as part of pronunciation teaching method. The higher authorities should also allow teachers to carry out teaching without being wedged to strictly follow the textbook to ensure the liveliness of the learning session.